Growth and Structural Changes in the South Asian Economies of India, Nepal and Sri Lanka - Agarwal, M. K.; Gupta, Ritika (Journal of Development and Administrative Studies, 2018)
South Asian region is characterized by developing economies with varying degrees of socio- economic development. These economies find low position in terms of human development at the global level. The South Asian economies are now being looked upon with high growth potentials. India is emerging as one of the fastest growing economy in the world and other economies are also showing better growth momentum. Sri Lanka has been especially showing better growth realization for the last one decade. But with regard to Nepal, growth momentum now seems to be getting weakened after showing better prospects earlier. Economic growth and structural changes generally go together in developing economies. This helps in realignment of sectoral behavior and productivity. We examine these issues in this paper. Moreover, we analyze growth trend in the South Asian economies of India, Nepal and Sri Lanka. Besides, we compare the structural changes in the three economies with the help of an index (NAV) along with the growth pattern. The study covers different periods for these economies while using secondary data. Trend growth rate, acceleration test and index of structural change (NAV) are used for analysis. These analyses suggest varying levels of growth performances in the three economies. However, relationship between growth rates and structural transformations does not get statistical support in any of the economies. The Journal of Development and Administrative Studies (JODAS), Vol. 24 (1-2), pp. 39-62